2000
DOI: 10.1093/ptj/80.8.759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the University of California–Los Angeles Shoulder Scale and the Simple Shoulder Test With the Shoulder Pain and Disability Index: Single-Administration Reliability and Validity

Abstract: Background and Purpose. Shoulder scales are often used to evaluate treatment efficacy, yet little is known about the psychometric properties of these scales. Only one scale has undergone psychometric scrutiny: the Shoulder Pain and Disability Index (SPADI). This study compared 2 shoulder measures—the University of California-Los Angeles (UCLA) Shoulder Scale and the Simple Shoulder Test (SST)—with the SPADI. Subjects. One hundred ninety-two patients with shoulder disorders were recruited from one physician's o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 15 publications
7
52
1
3
Order By: Relevance
“…Most of the studies that have evaluated the dimensional structure of the SPADI have suggested that it has 2 dimensions (7,45,47,48), with a majority of disability items loading on the first factor and a majority of pain items loading on the second. Conversely, Bumin et al (14) extracted 3 domains in the Turkish version of the SPADI, whereas Roddey et al (46) extracted only one factor. This suggests that the scale may have 1-3 dimensions, depending on the groups evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies that have evaluated the dimensional structure of the SPADI have suggested that it has 2 dimensions (7,45,47,48), with a majority of disability items loading on the first factor and a majority of pain items loading on the second. Conversely, Bumin et al (14) extracted 3 domains in the Turkish version of the SPADI, whereas Roddey et al (46) extracted only one factor. This suggests that the scale may have 1-3 dimensions, depending on the groups evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Although the SST claims to measure a single construct, it has been suggested that the SST is a 2-dimensional scale (46,47). According to Roddey and colleagues, the first dimension measures what patients can do with their shoulder and the second dimension measures the patient's comfort with their shoulder at rest (46). As for the ASES, factor analysis suggests that it evaluates 2 dimensions (pain and function) (47).…”
Section: Resultsmentioning
confidence: 99%
“…Very low and very high function were not precisely measured (39). The 2 subscores pain and function could not be supported by factor analysis (33, 38, 42).…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 87%
“…Relevant settings (aims and analysis [references]) for the SPADI are as follows: Shoulder pain (development of the SPADI [30]) Shoulder instruments (important comparative reviews [7, 13]) Various upper extremity diagnoses (reliability, minimal detectable difference [MDD], minimum clinically important difference [MCID] [21]) Various shoulder diagnoses (validity [32]) Adhesive capsulitis (factor analysis [33]) Adhesive capsulitis (reliability, validity, responsiveness [20, 34]) Rotator cuff (reliability, validity [35]) Rotator cuff, local infiltration (MCID [36]) After shoulder arthroplasty (validity, MDC [6, 31]) Total shoulder arthroplasty (responsiveness [19]) Various shoulder surgery (reliability, responsiveness [37]) Orthopedic practice (validity, factor, MDC, MCID [38]) Orthopedic practice (Rasch, partial credit model [39]) Primary care (validity, responsiveness [40]) Outpatient physiotherapy (validity, responsiveness [41]) Community volunteers (factor analysis [42]) …”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
“…The correlation of the severity of pain and functional impairment was rated by the UCLA Shoulder Rating Scale, 19 which has demonstrated good internal consistency when compared with the gold-standard Shoulder Pain and Disability Index. 20 A score .27 is considered excellent, and a score ,27 is fair or poor. The score is derived from the patient's self-reported level of pain, upper-extremity function, and physician assessment of ROM.…”
Section: Discussionmentioning
confidence: 99%